“Outside We May Become Wrinkly but Inside We Are Growing Crumbly” - Liana Winett; Louise Dalingwater (The Journal of Aging and Social Change, 2026)
Women’s health in both the United States and the United Kingdom lags that of men in clinical understanding, options, and access. Even some phenomena that exclusively affect women and which represent a near-universal experience, such as menopause, have historically received less attention than their ubiquity might suggest. Given that the governments of both nations have material influence over how health is perceived and addressed, we wished to explore whether and how menopause has been perceived as a national policy matter. Applying Bacchi’s What’s the Problem Represented to Be (WPR) framework, we assessed menopause-related policy discourse in both nations over more than four decades. We present discourse analysis findings on menopause-related Clinical Care, a theme that shows notable parallels between the two discourses, despite the many structural differences in how health care is funded, managed, and provided in the two nations. Overall, we found menopause clinical care portrayed as an issue of specialty care and access, quality and availability of clinical guidance, clinical considerations relative to specific populations, and the need for management of associated health risks. Less emphasized were social and economic influences affecting menopause-related clinical care needs and outcomes. Potential implications and opportunities for expanding problematizations are discussed.